2013
DOI: 10.1063/1.4821743
|View full text |Cite
|
Sign up to set email alerts
|

Onset of convection with fluid compressibility and interface movement

Abstract: The density increase from carbon dioxide (CO 2) dissolution in water or hydrocarbons creates buoyancy-driven instabilities that may lead to the onset of convection. The convection is important for both CO 2 sequestration in deep saline aquifers and CO 2 improved oil recovery from hydrocarbon reservoirs. We perform linear stability analyses to study the effect of fluid compressibility and interface movement on the onset of buoyancy-driven convection in porous media. Compressibility relates to a non-zero diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
(111 reference statements)
1
20
0
Order By: Relevance
“…In such case there will be phase transition between CO 2 and brine. The flat top interface will also shift with time because of pressure and volume change occurring upon CO 2 dissolution (Myint and Firoozabadi, 2013;Farajzadeh et al, 2007a,b;.…”
Section: Effects Of Aspect Ratios Amentioning
confidence: 98%
“…In such case there will be phase transition between CO 2 and brine. The flat top interface will also shift with time because of pressure and volume change occurring upon CO 2 dissolution (Myint and Firoozabadi, 2013;Farajzadeh et al, 2007a,b;.…”
Section: Effects Of Aspect Ratios Amentioning
confidence: 98%
“…Studies have reported the impact on these properties of boundary conditions 21,22,28 , anisotropy of the permeability 16,[23][24][25]28 , geometry of the system 26 , compressibility and interface movement 27 , a geothermal gradient 28,29 , and control parameters in laboratory experiments 5,[10][11][12]19 . However, an important aspect that has been less investigated is the impact of chemical reactions on such instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the early-stage development of this instability has been characterized both theoretically and experimentally for porous media or Hele-Shaw cells with a focus on the critical time and wavenumber for the onset of convection 5,[10][11][12]16,[18][19][20][21][22][23][24][25][26][27][28][29] . Studies have reported the impact on these properties of boundary conditions 21,22,28 , anisotropy of the permeability 16,[23][24][25]28 , geometry of the system 26 , compressibility and interface movement 27 , a geothermal gradient 28,29 , and control parameters in laboratory experiments 5,[10][11][12]19 .…”
Section: Introductionmentioning
confidence: 99%
“…Even though the effect of the various factors such as the anisotropy and heterogeneity of the porous media (Ennis-King et al 2005;Xu et al 2006;Farjazadeh et al 2011), the geochemical reaction (Andress and Cardoso 2012;Ghesmat et al 2012) and the interface movement due to swelling (Meulenbroek et al 2013;Myint and Firoozabadi 2013) on the stability criteria have been widely considered, a little attention has been paid on the interface condition between the supercritical CO 2 and the brine. However, in the CO 2 sequestration system, due to a capillary effect, a partially permeable boundary condition is more realistic than an impermeable one, which has been adopted in the previous stability analyses.…”
Section: Introductionmentioning
confidence: 99%